Geochemistry and chronology of the bunburra rockhole ungrouped achondrite - Spivak-Birndorf, L.; Bouvier, A.; Benedix, G.; Hammond, S.; Brennecka, G.; Howard, K.; Rogers, N.; Wadhwa, M.; Bland, Phil; Spurný, P.; Towner, Martin (University of Arkansas, 2015)
Bunburra Rockhole is a unique basaltic achondrite that has many mineralogical and petrographic characteristics in common with the noncumulate eucrites, but differs in its oxygen isotope composition. Here, we report a study of the mineralogy, petrology, geochemistry, and chronology of Bunburra Rockhole to better understand the petrogenesis of this meteorite and compare it to the eucrites. The geochemistry of bulk samples and of pyroxene, plagioclase, and Ca-phosphate in Bunburra Rockhole is similar to that of typical noncumulate eucrites. Chronological data for Bunburra Rockhole indicate early formation, followed by slow cooling and perhaps multiple subsequent heating events, which is also similar to some noncumulate eucrites. The 26Al-26Mg extinct radionuclide chronometer was reset in Bunburra Rockhole after the complete decay of 26Al, but a slight excess in the radiogenic 26Mg in a bulk sample allows the determination of a model 26Al-26Mg age that suggests formation of the parent melt for this meteorite from its source magma within the first ~3 Ma of the beginning of the solar system. The 207Pb-206Pb absolute chronometer is also disturbed in Bunburra Rockhole minerals, but a whole-rock isochron provides a re-equilibration age of ~4.1 Ga, most likely caused by impact heating.The mineralogy, geochemistry, and chronology of Bunburra Rockhole demonstrate the similarities of this achondrite to the eucrites, and suggest that it formed from a parent melt with a composition similar to that for noncumulate eucrites and subsequently experienced a thermal history and evolution comparable to that of eucritic basalts. This implies the formation of multiple differentiated parent bodies in the early solar system that had nearly identical bulk elemental compositions and petrogenetic histories, but different oxygen isotope compositions inherited from the solar nebula.